Enhancing John Rawls’s. Theory of justice to cover health and social determinants of health - Ekmekci, Perihan Elif; Arda, Berna (Acta Bioethica, 2015)
The vast improvements in medical technology reviled the crucial role of social determinants of health for the etiology, prevalence and prognosis of diseases. This changed the content of the right to health concept from a demand of health services, to a claim of having access to all social determinants of health. Thus, the just allocation of scarce resources of health and social determinants of health became an issue of ethical theories. John Rawls developed a theory of justice. His theory suggests that the principles of justice should be determined by individuals in a hypothetic initial position. In the initial position, individuals agree on principles of justice. Rawls puts forth that the institutions of the society should be structured in compliance with these principles to reach a fair social system. Although Rawls did not justify right to health in his theory, the efforts to enlarge the theory to cover right to health flourished quite fast. In this paper first the basic components of Rawls theory is explained. Then the most outstanding approaches to enlarge his theory to cover right to health is introduced and discussed within the discourse of Rawls theory of justice.